2012
DOI: 10.1007/s10549-012-2355-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy with tamoxifen compared to aromatase inhibitors for 257 male breast cancer patients

Abstract: To determine the impact of adjuvant treatment with tamoxifen and aromatase inhibitors (AI) on the survival of men with breast cancer. We analyzed 257 male patients with hormone-receptor-positive breast cancer from numerous German population-based cancer registries treated with tamoxifen (N = 207) or aromatase inhibitors (N = 50). The median follow-up was 42.2 (range 2-115) months. Median age at diagnosis was 68 (range 36-91) years. Thirty-seven (17.9 %) patients treated with tamoxifen and 16 (32.0 %) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 28 publications
1
73
0
5
Order By: Relevance
“…These results add to current evidence in the female bc population [12][13][14] . The use of tamoxifen has been recommended in endocrine-sensitive male bc, with less evidence of efficacy for aromatase inhibitors (ais) 15 . The role of targeted therapies (for example, trastuzumab) in male bc has largely been unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results add to current evidence in the female bc population [12][13][14] . The use of tamoxifen has been recommended in endocrine-sensitive male bc, with less evidence of efficacy for aromatase inhibitors (ais) 15 . The role of targeted therapies (for example, trastuzumab) in male bc has largely been unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to support the role of ais in male bc is sparse, being based mainly on retrospective case reports and case series. Recently, Eggemann et al 15 compared ais with tamoxifen in male bc and found that ais carried a mortality risk that was increased by a factor of 1.5 ( p = 0.007). Similar concerns have been noted in the female population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a wave of studies, though retrospective in nature, provided clues that ER-directed therapies are effective for treating MBC patients [8][9][10][11][12]. Antitumor efficacy has been reported with virtually all the antiestrogens currently available, namely tamoxifen, aromatase inhibitors (AIs) and fulvestrant [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…AIs, however, are suggested to have survival benefit compared with tamoxifen in female postmenopausal breast cancer patients with metastatic HR-positive breast cancer. In contrast, OS in men was significantly increased with tamoxifen compared with AIs (Eggemann et al 2013). This could be explained by the 'feedback loop' hypothesis.…”
Section: Aromatase Inhibition In Menmentioning
confidence: 83%